Optimising Interactive Cloud Gaming for Mobile Learning: GPU Virtualisation, Codec Efficiency, and UI Design - Damle, Mohini; Pathak, Pankaj; Damle, Madhavi; Singh, Sushant (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Mobile learning environments increasingly demand sophisticated interactive technologies capable of delivering engaging educational experiences while overcoming traditional hardware limitations. This integrative literature review examines cloud gaming infrastructure advancements for mobile learning. Results from both technical research and practical educational experiences are compared to understand how technology supports learning. Analysis reveals that hardware-assisted GPU virtualisation frameworks achieve substantial performance improvements on mobile devices, enabling sophisticated educational simulations. Video codec optimisations significantly reduce latency and bandwidth consumption, while touchscreen controls and haptic systems enhance learning effectiveness. Recognition of pedagogical innovations across different domains highlights their tremendous potential. STEM simulation platforms utilising molecular modelling and mathematical visualisation demonstrate significantly higher student engagement. Medical training applications enable learners. Collaborative learning environments facilitate enhanced problem-solving through shared virtual spaces, while language learning applications demonstrate superior vocabulary retention. The analysis establishes cloud gaming infrastructure as a transformative enabler for mobile learning, democratising access to sophisticated educational tools.